Threads, wefts and fabrics… visual constructions between photography and printmaking - Trocello, Micaela (PORTO ARTE: Revista de Artes Visuais, 2018)
This article presents a poetic production where printmaking and photography are deeply related. They are works with strong female presence, including Argentina’s popular cultures and historical figures.